An examination of offensive transition at World Cup matches using social network analysis - Armatas, V.; Zacharakis, E.; Apostolidis, N. (Journal of Physical Education and Sport, 2022)
This study applied Social Network Analysis (SNA) to the passing networks during the offensive transitions of Men, Women, and Men u20 at the World Cup matches of 2018 and 2019. For each offensive transition, the progression of the sequence was categorized as 1) a goal-scoring attempt (GSAtt), 2) a set play (SP), or 3) possession lost (PosL). For SNA, two different networks were constructed: 1) Possession Network (PoN) and 2) Goal Scoring Attempt Network (GSAN). The SNA tool SocNetV was used to conduct the metrics: 1) Out-Degree centrality (%OdC), 2) In-Degree centrality (%IdC) and 3) Closeness centrality (%CC). For progression, results revealed that age had a significant effect on PoL, where Men demonstrated significantly higher PoL than Men u20. Concerning the type of SP, there were significant effects of age and sex on corner kicks awarded, where Women and Men u20 awarded significantly more corner kicks than Men. The centrality metrics for PoN revealed that teams from the three World Cup tournamets used the defensive and pre-defensive sectors to recover ball possession and often lost possession at the attacking and pre-attacking sectors. The centrality metrics for GSAN proposed that the final pass was executed mainly outside the box (Zone 7) in all three tournaments but differences were found concerning the execution zone of the final attempt. This study adds to the previous research on network analysis in football and demonstrates an effective method of determining the efficacy of offensive transition during World Cup matches and the existing differences between Men, Women, and Men u20.